Studi Kajian Program Badan Riset dan Inovasi Daerah Kota Medan - Nadya Fasya; Albi Tania Sembiring; Marcella Marcella; Toman Sony Tambunan; Abdul Haris Baeha; Dewi Mahrani Rangkuty (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The discussion around BRIDA is a topic that is being discussed along with the transformation of the Research and Development Agency (BPP) of the Ministry of Home Affairs, in accordance with the provisions of Article 65 paragraph (1) of Presidential Regulation Number 78 of 2021. The article asserts that the work unit responsible for research, development, and application of science and technology within the ministry/agency will be transferred to the responsibility of the National Research and Innovation Agency (BRIN). This research uses a descriptive qualitative approach with a literature study method through literature review that refers to field data in relation to the research title. Data sources were obtained from information publications on various related websites. The programmes, targets and achievements of the Regional Research and Innovation Agency of Medan City during the period 2020 to 2022 showed a positive trend, with percentages above 50% and points that reached a satisfactory level of success. Evaluation of the annual work programme was conducted at the end of each activity in a fiscal year and at the end of the fiscal year, providing an overall picture of performance and achievements.